Art-Based Aceh Oral Folkrole Modulize to Revitalize Uswah Hasanah: Revitalisasi Uswah Hasanah dengan Pengembangan Modul Melalui Folklor Lisan Aceh Berbasis Seni - Diana, Novi; Anisaturrahmi, Anisaturrahmi; Istiqamah, Istiqamah (Halaqa: Islamic Education Journal, 2022)
The uswah hasanah approach exemplifies the learning method as a personality-forming agent. Uswah hasanah is an ever-present form of instruction. Through the resuscitation of Acehnese oral folklore based on art, the purpose of this research was to investigate the design process and efficacy of the module created utilizing the uswah hasanah technique. This research utilizes a research and development methodology. The model employed is the creation of a four-dimensional model. The 4-D development model (Four D) is a development paradigm for learning devices. The 4D development paradigm has four major phases: Define, Design, Develop, and Disseminate. The study of the module validation findings by the Indonesian Language Lecturer revealed a mean score of 3.92, placing it in the extremely valid category (3.5 V 4). On the basis of these results, it can be stated that the module designed by the researcher is suitable for field testing on a limited scale. The success of the module employing the Uswah Hasanah Method via the Revitalization of Aceh Oral Folklore Based on Art will be determined by conducting a restricted test on students of the Indonesian Language Education Department in Semester I of the Literary Theory Course.